Effect of unidirectional prepreg size on punching of pseudo-ductile CFRP laminates and CFRP/metal hybrid composites. (15th February 2018) - Ho, Yu-Chien; Yanagimoto, Jun
Abstract: Punching is an efficient and economical process for producing a hole in structures for functional requirements, repair, maintenance, and so forth. Toward extending the use of punching to new materials, the punching of multilayer CFRP laminates and CFRP/metal hybrid composites was investigated. In this paper, the effect of the unidirectional (UD) prepreg size on the shear behavior of pseudo-ductile CFRP laminates and CFRP/metal hybrid composites is discussed on the basis of experimental observations. CFRP laminates were individually fabricated using standard (149 g/m 2 ) and thin-ply (62 g/m 2 ) prepregs, and were bonded with three metals (aluminum alloy A6061, magnesium alloy AZ31, and advanced high-strength steel SPFC980) by utilizing an autoclave (co-curing) and adhesive glue for hybrid composite application, then punched by a circular die and punch tool at room temperature. The effects of the UD prepreg size on the punch force, punching resistance (Ks), quality, and sheared surfaces of the through-holes are discussed. The shear behavior for punching in different composites was also studied by microscopic examination. Our results are expected to enable quantitative design for the development of punched CFRP laminates and CFRP/metal hybrid composites.